PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL BEKAS (Survey Pada Konsumen Melaju Raya Rizky Motor di Wilayah Bekasi Timur) - Wibowo, Setyo Ferry; Sasmita, Indra; Murti, Agung Kresna (Fakultas Ekonomi, Universitas Negeri Jakarta, 2013)
Indra Sasmita, 2012 the influence of the product quality and the price on the purchase decision used car (survey on the consumer Melaju Raya Rizky Motor in east Bekasi), Thesis: Management Studies Program, Department of management, Faculty of Economics, State University of Jakarta, in July 2012. This research aims to analyze and describe the product quality and price of a used car purchase decision making in the showroom Melaju Raya Rizky Motor. This study uses survey methods, sample, and a questionnaire as a means of data collection. The location of the research carried out at the Showroom Melaju Raya Rizky Motor at JL.Raya Kota Legend No. 8. Bekasi Timur. Analysis of the research was carried out by using the application program SPSS statistics (Statistical Package for The Social Science) version 19, to manipulate the data. The results of this research shows there is a significant relationship between the product quality and price on the purchase decision. Keywords: product quality, price, purchase decision